Análises de gastos sociais do Governo do Estado do Rio Grande do Norte (2014 e 2018) com o suporte da Teoria dos Ciclos Políticos - Santana, Larissa Moura de Oliveira (2022)
The Federal Constitution of 1988 defines education as social rights; the health; The feeding; the work; the dwelling; the transport; leisure; the security; social security; maternity and childhood protection and assistance to the destitute. This investigation aims to analyze the behavior of social spending by the Government of the State of Rio Grande do Norte (RN) on the occasion of the 2014 and 2018 elections, with the support of the Theory of Political Cycles. In order to achieve the objective, the following social functions were defined: Public Security; Social assistance; Social Security; Health; Education; Culture; Urbanism; Housing; Sanitation and Sport and Leisure. The data were obtained through the information contained in the Summary Report of Budget Execution (RREO) - Statement of Expenditure Execution by Function/Sub-Function, available on the website of the Brazilian Public Sector Accounting Information System (SICONFI) of the Secretaria do Tesouro Nacional (STN). The results revealed that the behavior of social spending changed before, during and after the 2014 and 2018 elections and there was evidence of electoral opportunism in spending on social functions Health; Culture; Housing; Urbanism and Sport and Leisure. The study contributes to the advancement of the literature in the analysis of social expenditures and political-economic cycles, and also clarifies society regarding the handling of public resources due to electoral years (before, during and after).